Kajian Beban Kerja pada Industri Perhotelan - I Wayan Kiki Sanjaya; I Made Arya Astina; I Ketut Muliadiasa; Gusti Ayu Praminatih (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This research is motivated by the gap in the front office department team in carrying out their duties. The reality of complaints from guests due to the check-in and check-out process taking too long, as well as unfulfilled guest requests for previously booked rooms, does not seem to be in accordance with management's expectations. The purpose of this study was to analyze the workload of the receptionist/GSA, bellboy/BSA, telephone operator, and guest relation officer (GRO) at The Haven Seminyak Bali. The research conducted at The Haven Seminyak Bali used quantitative analysis techniques (descriptive statistics), consisting of workload analysis and workforce needs analysis. In obtaining data to support this research, interview techniques, questionnaire techniques, and documentation were used. The results of the study showed that the number of employees was insufficient to carry out the workload so that there was a shortage of employees in that section. As a result, when conditions are busy, severe conditions that are not ideal for working occur.